1998
DOI: 10.1038/sj.ejhg.5200224
|View full text |Cite
|
Sign up to set email alerts
|

Strong founder effect for a transglutaminase 1 gene mutation in lamellar ichthyosis and congenital ichthyosiform erythroderma from Norway

Abstract: Autosomal recessive congenital ichthyosis (ARCI) is a clinically heterogeneous disorder of keratinisation. It was recently shown that mutations in the transglutaminase 1 (TGM1) gene may be associated with the clinical subtypes lamellar ichthyosis (LI) and non-bullous congenital ichthyosiform erythroderma (CIE). Thirty-six Norwegian families with LI and seven with non-bullous CIE were studied with microsatellite markers linked to the TGMI gene. One common haplotype for two markers was found on 74% of disease as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
11

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 21 publications
2
69
0
11
Order By: Relevance
“…The point mutation c.877-2A>G was identified in 14% of alleles associated with LI/CIE, mainly in the Swedish patients. This mutation has also been described from several other countries (37,38,40,41,(48)(49)(50)(51)(52)(53) and is reported as a founder mutation in Norway (49), located close to Sweden. The p.Ser358Arg mutation was originally identified in a Swedish family (28) and there is no report of this mutation outside Sweden and Norway (unpublished data), which suggests a local founder mutation.…”
Section: Discussionmentioning
confidence: 95%
“…The point mutation c.877-2A>G was identified in 14% of alleles associated with LI/CIE, mainly in the Swedish patients. This mutation has also been described from several other countries (37,38,40,41,(48)(49)(50)(51)(52)(53) and is reported as a founder mutation in Norway (49), located close to Sweden. The p.Ser358Arg mutation was originally identified in a Swedish family (28) and there is no report of this mutation outside Sweden and Norway (unpublished data), which suggests a local founder mutation.…”
Section: Discussionmentioning
confidence: 95%
“…Similar kinds of result were also seen in the study of 43 Norwegian ARCI families where one major founder mutation A2526G (corresponding to our mutation 3349 A to G) was found in patients with both type I and type II. 16 Interestingly, this mutation was found only in one Finnish compound heterozygote patient whose clinical picture was quite untypical compared with other TGM 1 mutation carriers (Figure 3c). …”
Section: Discussionmentioning
confidence: 99%
“…11 After our previous studies one additional mutation, 3349A to G, was found in restriction enzyme Msp I analysis of 27 families as described earlier. 16 …”
Section: Molecular Genetic Studiesmentioning
confidence: 99%
“…160 The ultrastructural features of the so-called EM classification described by the Heidelberg group are based on a glutaraldehyde fixation of the skin biopsy specimen. [206][207][208][209][210] With this technique polygonal clefts in the SC can be observed as an ultrastructural key feature of TGase-1 deficiency, 211 aberrant vesicular structures may indicate NIPAL4 (;ICHTHYIN ) mutations in ARCI, 33 and trilamellar membrane aggregations in the SC and SG (EM type IV) are pathognomonic for ichthyosis prematurity syndrome. 89 Detachment of the SC from the SG with asymmetric cleavage of corneodesmosomes is a specific feature of NS.…”
Section: Use Of Ultrastructural Analysesmentioning
confidence: 99%